Development of Community in Lithuania: Strategy and Tactics - Beresnevičiūtė, Danguolė (Socialinė teorija, empirija, politika ir praktika, 2001)
The goal of the paper is to present the psychological determinants for community building in Lithuania. There are three parts of the paper. The discussion about community concept through the perspectives of social psychology and pedagogy takes place in the first part. The role of social worker in community building process is discussed in the second part. The strategy and tactics of psychological way to build community is provided in the final part of the paper.